Gender Differences in Sleep Deprivation and Quality Among Spousal Caregivers of Disabled Partners: A Nationwide Cross-Sectional Study. - Mu, Tingyu; Xu, Rixiang; Zhu, Qianyin (Inquiry (00469580), 2026)
This study examined gender differences in sleep outcomes among spousal caregivers of disabled partners in China and the relationship between the breadth of a care recipient's functional disability and a caregiver's sleep. This study used the 2020 data from the fifth wave of the China Health and Retirement Longitudinal Study (CHARLS), including 13 243 participants, of whom 1600 were caregivers for disabled spouses. The degree of disability was assessed using the Basic/Instrumental Activities of Daily Living (BADL/IADL) scale. Sleep quality and duration were measured by self-report. Statistical analyses included chi-square tests and binary logistic regression, adjusting for potential confounders such as sociodemographic characteristics, health status, and lifestyle factors. Women spousal caregivers had shorter sleep duration (OR = 1.309, 95% CI: 1.098-1.561) and poorer sleep quality (OR = 1.200, 95% CI: 1.011-1.424) versus non-caregivers, whereas no significant differences were observed among men caregivers. Analysis of the parametric relationship revealed that when the number of types of disabilities in care recipients reached 5 to 8, caregivers' sleep duration was significantly reduced (OR = 1.238, 95% CI: 1.007-1.522); when the number reached 9 to 12, both sleep duration (OR = 1.616, 95% CI: 1.096-2.382) and sleep quality (OR = 1.774, 95% CI: 1.220-2.579) of caregivers deteriorated significantly. Caregiving for a disabled spouse impairs sleep among women. A clear graded relationship exists between care recipients' functional disability types and caregivers' sleep problems. Support policies should consider gender differences and target women undertaking high-intensity care.